2021
DOI: 10.11591/ijeecs.v24.i2.pp1047-1053
|View full text |Cite
|
Sign up to set email alerts
|

Readiness in using online interactive platforms for remote teaching

Abstract: Technological advances offer a new shift of change for society. In this era, it is almost impossible to come by without its help. The Malaysian government has invested highly in information and communications technology (ICT) for online teaching and learning at the current time. Digital technologies have been integrated into the teaching and learning process in almost all public or private schools in Malaysia. The use of multimedia tools has enabled learners to understand difficult concepts or ideas and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Kementerian Pendidikan telah memberikan garis panduan yang memperincikan tanggungjawab dan peranan pentadbir, guru, ibu bapa dan pelajar untuk memastikan kelancaran PdPc sepanjang tempoh Perintah Kawalan Pergerakan (PKP). Maka, keperluan penggunaaan aplikasi teknologi maklumat untuk membantu proses PdPc, berinteraksi dengan bahan pembelajaran kendiri, mendapat maklumat untuk berinteraksi amatlah penting (Omar et al, 2021). Pembolehubah bersandar adalah pembolehubah yang faktornya diperhati ataupun diukur untuk menentukan pengaruh yang disebabkan oleh pembolehubah tidak bersandar.…”
Section: Sorotan Kajianunclassified
“…Kementerian Pendidikan telah memberikan garis panduan yang memperincikan tanggungjawab dan peranan pentadbir, guru, ibu bapa dan pelajar untuk memastikan kelancaran PdPc sepanjang tempoh Perintah Kawalan Pergerakan (PKP). Maka, keperluan penggunaaan aplikasi teknologi maklumat untuk membantu proses PdPc, berinteraksi dengan bahan pembelajaran kendiri, mendapat maklumat untuk berinteraksi amatlah penting (Omar et al, 2021). Pembolehubah bersandar adalah pembolehubah yang faktornya diperhati ataupun diukur untuk menentukan pengaruh yang disebabkan oleh pembolehubah tidak bersandar.…”
Section: Sorotan Kajianunclassified
“…The Malaysia Education Blueprint (2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022)(2023)(2024)(2025) emphasises the need of budgeting for ICT in teaching and learning (Ministry of Education, 2012) and RM6 billion has been allocated for this purpose. The role of technology in education has become more prominent during the COVID-19 pandemic as all students and educators, even pre-service instructors, rely on it (Omar et al, 2021). It was reported that during the COVID-19 pandemic, preservice teachers demonstrated positive attitude in online interactive platforms in their service-learning (Omar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The role of technology in education has become more prominent during the COVID-19 pandemic as all students and educators, even pre-service instructors, rely on it (Omar et al, 2021). It was reported that during the COVID-19 pandemic, preservice teachers demonstrated positive attitude in online interactive platforms in their service-learning (Omar et al, 2021). Technology usage is increasing in tandem with the development of 21st-century capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Education is the key to the development of society. Omar [1] argued how Malaysian public schools have used technological tools for the benefit of students to understand difficult concepts. The study also commented how teachers prefer blended learning combining online teaching and the traditional classroom model.…”
Section: Introductionmentioning
confidence: 99%